The Role of Religious Education in Cultivating Emotional Intelligence and Resilience Among Students in Diverse Communities - Shodiq, Sadam Fajar (FKIP Universitas Lampung, 2024)
The Role of Religious Education in Cultivating Emotional Intelligence and Resilience Among Students in Diverse Communities. Objective: The objective of this research is to examine the impact of religion education on enhancing the emotional intelligence and mental resilience of students in Yogyakarta. This is significant since several students have difficulties in regulating stress and emotions owing to rapid technology advancements and the complexities of social interactions. Methods: The research used a quantitative methodology via a survey conducted with a random sample of 325 students from religious institutions in Yogyakarta. Data were gathered using questionnaires to assess pupils' religious education, emotional intelligence, and mental resilience. Data analysis was performed with Smart-PLS to evaluate the interrelationship among variables and assess the appropriateness of the study model. Results: The study's findings demonstrate that religious education significantly enhances kids' emotional intelligence and mental resilience. Religious education aids pupils in comprehending and regulating their emotions, enhancing interpersonal skills, and fortifying their resistance against stress and life adversities. The results reveal a favorable correlation between religious education and the enhancement of students' adaptability in many social contexts. Conclusion: In conclusion, religious education significantly influences the development of students' character, particularly in enhancing their emotional intelligence and mental resilience. This study's findings significantly contribute to the formulation of a religious education curriculum that addresses both spiritual and students' emotional and psychological dimensions. These results highlight the need of amalgamating religious education with character development initiatives to better equip pupils for the difficulties of contemporary life. Keywords: religious education, emotional intelligence, mental resilience, religious-based schools.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024120